Formation of vocational competence of future specialists in physical education and sports - Kovalenko, Ju.; Gnatenko, K.; Fedorenko, O. I.; Федоренко, О. І.; Karpets, L.; Kovalenko, R.; Федоренко Олена (Pedagogika. – 2020. – Vol. 140, No. 4. – P. 220–236, 2020)
Завданням дослідження є визначення складових формування професійної компетентності майбутніх фахівців з фізичного виховання та спорту.

The objective of the study is to determine the components of the formation of vocational competence of future specialists in physical education and sports. Analysis of components of students in the specialties “Management in sports activities” and “Secondary education (Physical education)” was made. Comparative characteristic of partial readiness for the professional and pedagogical self-development of the first and fourth-year students was conducted.

Цель исследования - определить компоненты формирования профессиональной компетентности будущих специалистов по физической культуре и спорту.
Būsimųjų kūno kultūros ir sporto specialistų profesinės kompetencijos formavimas
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u Scopus; competence; professional competence; sports specialists; physical culture; management; professional culture; компетентність; професійна компетентність; спортивні фахівці; фізична культура; менеджмент; професійна культура; компетентность; профессиональная компетентность; специалисты по спорту; физическая культура; менеджмент; профессиональная культура